Crystallization kinetics accountability and the correspondingly developed glass-forming criteria: A personal recollection at the forty years anniversaries - Šesták J.; Kozmidis-Petrović A.; Živković Ž. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The meaning of experimentally determined characteristic temperatures is analyzed in terms of Hruby glass forming criterion. Despite various analyzed modifications it reveals that the sensitivity of original criterion is unsurpassable. The applicability of Sestak-Berggren empirical equation for the description of crystallisation kinetics is comparable with the classical modelling based on Johnson-Mehl-Avrami equation. Their employment is certainly dependent to the purpose of evaluation showing their substitution ability and limits.